The Effect of Workplace Spirituality on Teachers’ Psychological Resilience and Prosocial Motivation Levels / İşyeri Ruhsallığının Öğretmenlerin Psikolojik Sağlamlık ve Prososyal Motivasyon Düzeylerine Etkisi - Demir, Selçuk; Çobanoğlu, Necati (Erdal TOPRAKCI, 2023)
Teachers working in schools where they feel high-quality interactions and inner peace, finding their work meaningful and feeling transcendence while performing their duties contribute to the development of positive attitudes. These positive attitudes are highly important in terms of providing more qualified education and training services. Psychological resilience and prosocial motivation are among the critical attitudes teachers must have. In this study, the investigation of the effect of perceived workplace spirituality on teachers' psychological resilience and prosocial motivation levels has been aimed. The study is characterized by a correlational model. The group of the study is the teachers working in primary schools in Şanlıurfa province center. The sample of the study, on the other hand, consists of 303 teachers from 45 primary schools in Şanlıurfa province center, which were decided according to the rule of impartiality. The data of the study has been collected via the "Workplace Spirituality Scale", "Psychological Resilience Scale" and "Prosocial Motivation Scale". With the confirmatory factor analysis, the factor structures of the scales were examined in terms of fit values. In the context of this research, it has been detected that the scales used are valid and reliable. The measurement pattern in the study reveals that the variables are statistically significantly related to each other. Then, a structural pattern within the scope of the theoretical framework in the literature has been proposed. According to the structural pattern that produced the best-fit values, perceived workplace spirituality positively affects teachers' psychological resilience and prosocial motivation levels. On the other hand, the psychological resilience of the teachers does not have a statistically significant impact on their prosocial motivation levels. In light of these findings, it is considered crucial for school principals wanting to mobilize teachers' psychological factors to create a culture of perceived spirituality in the school environment.

Öğretmenlerin görev yaptıkları okullarda sahip oldukları kaliteli etkileşim ağı ve hissettikleri iç huzur, işlerini daha anlamlı bulmalarına ve aşkınlık hissi ile görevlerini yerine getirmelerine katkı sağlamaktadır. Okul ortamlarında olumlu tutumlarının artması ise öğretmenlerin daha nitelikli eğitim-öğretim hizmeti sunmaları bakımından önemlidir. Psikolojik sağlamlık ve prososyal motivasyon, öğretmenlerin etkili bir öğretim hizmeti sunabilmeleri için sahip olmaları gereken kritik tutumlar arasındadır. Bu araştırmada; algılanan işyeri ruhsallığının öğretmenlerin psikolojik sağlamlık ve prososyal motivasyon düzeyleri üzerindeki etkisinin tespit edilmesi amaçlanmaktadır. Çalışma, korelasyonel model ile biçimlendirilmiştir. Araştırmanın evrenini, Şanlıurfa il merkezindeki ilkokullarda görev yapan öğretmenler meydana getirmektedir. Çalışmanın örneklemini ise Şanlıurfa il merkezinden yansızlık kuralına göre kararlaştırılan 45 ilkokuldaki 303 öğretmen oluşturmaktadır. Araştırmanın verileri; “İşyeri Ruhsallığı Ölçeği”, “Psikolojik Sağlamlık Ölçeği” ve “Prososyal Motivasyon Ölçeği” aracılığıyla toplanmıştır. Doğrulayıcı faktör analizi ile ölçeklerin faktör yapıları uyum değerleri açısından incelenmiştir. Bu araştırma bağlamında, yararlanılan ölçeklerin geçerli ve güvenilir oldukları tespit edilmiştir. Araştırmada ölçüm modeli, değişkenlerin birbiriyle istatistiksel açıdan anlamlı ilişkili olduğunu ortaya koymaktadır. Sonrasında alanyazındaki kuramsal çerçeveye uygun olarak yapısal bir model önerilmektedir. En iyi uyum değerlerini üreten yapısal modele göre; algılanan işyeri ruhsallığı, öğretmenlerin psikolojik sağlamlık ve prososyal motivasyon düzeylerini pozitif olarak etkilemektedir. Bunun yanı sıra öğretmenlerin psikolojik dayanıklıklarının, prososyal motivasyonları üzerinde istatistiksel olarak anlamlı bir etkisi bulunmamaktadır. Elde edilen bulgular ışığında; öğretmenlerin psikolojik faktörlerini harekete geçirmek isteyen okul müdürlerinin okul ortamında ruhsallık algılanan bir kültür oluşturması önemli görülmektedir.
İşyeri Ruhsallığının Öğretmenlerin Psikolojik Sağlamlık ve Prososyal Motivasyon Düzeylerine Etkisi / The Effect of Workplace Spirituality on Teachers’ Psychological Resilience and Prosocial Motivation Levels
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar